Developing a Conceptual Model of Employee Ecological Behavior using an Integrative Approach - FAROOQ, Khalid; YUSLIZA, Mohd Yusoff; MUHAMMAD, Zikri; SAPUTRA, Jumadil (Journal of Environmental Management and Tourism; Vol 13 No 1 (2022): JEMT, Volume XIII, Issue 1(57), Spring 2022DO - 10.14505/jemt.v13.1(57).03, 2022)
In recent years, research on Green Intellectual Capital (IC) has received greater attention in organizational scholarship. This paper develops a conceptual model based on an integrative approach better to understand antecedents and outcomes of Green IC. The proposed model offers future research a holistic understanding of the antecedents and outcomes of Green IC that predict perceived CSR and environmental performance. Moreover, the study revealed a previously unexplored effect of Green IC on perceived CSR. This conceptual paper reviews theoretical approaches and uses intellectual capital-based view theory as underpinning to understand Green IC’s antecedents and outcomes. The authors developed a conceptual model with Green Human Resource Management (HRM) and environmental consciousness as antecedents and perceived corporate social responsibility (CSR) and environmental performance as outcomes of Green IC. The authors also suggest that employee ecological behavior (EEB) may be influenced by perceived CSR and increase environmental performance. The study's findings would help an organization create a Green IC by the influential role of Green HRM practices and environmental consciousness. Recognition of the importance of Green IC could enable organizations to create more policies and strategies strengthening their formal CSR, EEB and improve environmental performance.